Bullying in the nursing work environment: integrative review - Roberta Nazario Aoki; Edinêis de Brito Guirardello (Universidade Federal do Rio Grande do Sul, 2019)
Abstract Objective: To evaluate the studies that approach bullying in the nursing practice environment. Method: Integrative review, conducted between April and December 2018, by combining the descriptors "bullying/bullying" AND "nursing/nursing/nurse" AND "workplace/workplace". We identified 224 studies of which 38 met the inclusion criteria. Results: The studies on nursing bullying presented three main approaches related to the prevalence in nursing practice, the repercussions for health and professional development, and the construction of theoretical models for bullying and nursing work environment variables. Conclusion: Bullying is a negative behavior present in the nursing practice environment and has a direct impact on professional performance, impairing general health and professional performance. Despite being a behavior with recognized negative potential in the work environment, few studies propose effective actions to prevent or control this phenomenon in health institutions.